Pengurusan pengajaran dan pembelajaran sekolah rendah kebangsaan di zon bandar daerah Kota Tinggi - Md. Amin, Raedah (2013)
The main purpose of this study was to review the management of teaching and learning at four primary schools (SK) in Kota Tinggi district. The study involved a sample of 128 teachers in four primary school of which 119 respondents were through questionnaires, while six respondents through interviews. All data were analyzed using the Statistical Package for Social Sciences version 19.0 software. Data analysis found that there were eight complaints that have been identified to be the cause of problems in the teachers teaching and learning timetable. The findings reveal that there were five problems faced by the administration in preparation timetable. From interviews, the study also found that there were six steps in the preparation of teaching and learning time of the review of the special preconditions as set out in the circular, the time allocated for specific ranks of teachers, classroom teachers determination, determination of class subjects, setting combination class for Islamic and moral education as well as the setting and updating of subject teachers. Finally, constructive ideas to solve the problem of teachers timetable presented in this study.